HYDRO GEOLOGICAL CONDITIONS OF DOIRANI LAKE BASIN. EXTERIOR INTERFERENCES AND RESULTS - Δημόπουλος, Γ.; Μπαρούτη, Β. (Bulletin of the Geological Society of Greece, 2004)
In this paper the hydro geological conditions of the quaternary deposits of Doirani lake basin are represented. The surface and subsurface water balance for the years 1988-1990 are also calculated.During the period 1985-1998 decline of 3,77 m of the lake's level has been noticed. The fact that the lake does not appear to have any sign of restoration leads to many questions regarding to its existence, water balance, hydraulic conditions of the basin and the groundwater overexploretion Analyzing the available hydrological, geological, lithological data a water balance deficit of 101.23*106 m3 /year for the period 1988-1990 is calculated resulted from the groundwater overexploretion. At the same time the loss of water due to the decline of the lake's level have reached the amounts of 90.58*106 m3 /year.